Evaluación del impacto del uso de agroquímicos sobre el lago de Tota mediante simulación matemática - Grandas Rincón, Isnardo Antonio; Pérez Holguín, Wilson Javier; Pesca Sierra, Yadimir (2021)
This article presents the results of the mathematical simulation for the model proposed byCentro Panamericano de Ingeniería Sanitaria y Ciencias del Ambiente (CEPIS), to determinethe maximum mass discharge permissible to five agrochemicals frequently used in the nearbyarea to the Lake of Tota-Colombia, considering the assimilative capacity of the lake about theelements contained in such products. For this, concentrations of the active ingredients of theagrochemicals are calculated and compared with the permissible limit values established in thecurrent normative for the preservation and conservation for surface water systems. Likewise, thephysicochemical properties associated to the mobility toward the lake of the consideredsubstances are identified. From this information, the calculations for determining the maximumdischarges in the lake of the active ingredients of agrochemicals analyzed are performed, as setout in the model. The results show that by using the current agricultural practices there is a highrisk of pollution of the lake.